Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions. Issue 10 (9th October 2014) - Chen, J; Chee, D; Wang, Y; Lim, G Y; Chong, S M; Lin, Y N; Huangfu, T
Abstract Cyprinid herpesvirus 3 (CyHV‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 CyHV‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 (n = 11) and European 4 (n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF29 and ORF30 (marker I) as well as ORF133 and its upstream region (marker II) revealed viruses of genotypes J (I++II+), U/I (I−−II−), an intermediate genotype (I++II−) and a novel genotype, I++II+Δ, which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II, while maintaining the I++ allele of marker I. The I++II+Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.